Insulin Resistance and Cancer Epidemiology, Cellular and Molecular Mechanisms and Clinical Implications - Fantus, I. George; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
This book reviews the epidemiological associations between insulin resistance and cancer. This is followed by reviews of animal models which support this relationship and provide insight into potential mechanisms. Several chapters then provide detailed examination of the cellular and molecular changes characterizing the insulin resistant state, such as hyperinsulinemia, abnormal metabolism and hormone signaling, and how these interact with various tumor characteristics. For example some tumors present increased quantities of the fetal form of the insulin receptor, unique regulation of oxidative (Krebs$1 (Bcycle) metabolism (Warburg effect), as well as mutations in various relevant signaling pathways. Finally, the clinical implications of these data are integrated with considerations of insulin (3z(Bsensitization(3y (Band potential metabolic interventions to prevent and treat cancer. It should be noted that while a number of cancers are associated with obesity the authors here have focused primarily on breast cancer as a key and significant model.s
Insulin and the Physiology of Carbohydrate and Lipid Metabolism -- Insulin Signalling: Cellular and Molecular Mechanisms -- Mechanisms of Insulin Resistance, Obesity and Metabolic Syndrome -- Obesity and Cancer: Epidemiology -- Insulin, Insulin Resistance and Cancer Associations -- Animal Models of Hyperinsulinemia, Insulin Resistance and Cancer -- Actions of Insulin as a Survival and Growth Factor: Akt/PKB, mTOR and MAPK Signaling -- Potential Mechanisms Linking Insulin to Cancer -- Insulin-like Growth Factors and Cancer -- Insulin, IGF Receptors and Cancer -- Clinical Implications for Cancer Treatment and Prevention.
Keywords: Medicine; Oncology; Toxicology; Biomedicine; Cancer Research; Pharmacology/Toxicology.